XML-Based RDF Data Management for XPath Query Language - Win Lai Hnin (Institute of Advanced Engineering and Science, 2013)
The Semantic Web is an extention of the current Web that will allow to find, share and combine information more easily. The meaning in the Semantic Web is mostly represented by Resource Description Framework (RDF). To harvest such power requires robust and scalable data repositories that can store RDF data. Most of the existing RDF storage techniques rely on relation model and relational database technologies for these tasks. The mis-match between the graph model of the RDF data and the rigid 2D tables of relational model jeopardizes the scalability of such repositories and frequently renders a repository inefficient for some types of data and queries. This paper proposed a system that can store RDF data in the XML repository and discuss the basic idea of conversion from RDF Schema to XML Schema and XPath queries for extract information from XML database.DOI: http://dx.doi.org/10.11591/ij-ict.v2i1.1503